Social Cognitive Theory and Medical Education: How Social Interactions Give Rise to Learning - Kim, Hae Won (Korean Medical Education Review, 2024)
The structures and processes of medical education have changed little since the publication of Flexner’s report, which stressed the scientific orientation of medical education and the curricular structure of two years of formal knowledge education and two years of clinical experience. However, the previous perspectives on medical education are facing challenges, and these call for new pedagogy and theories on which to base medical education practice. Considering that social dimensions of learning have been emphasized in educational practice, perspectives that integrate these aspects are needed. Among the various learning theories, social cognitive theory refers to the theoretical framework that contends that learning occurs within interactions with others and environments. From a social cognitive standpoint, learning through observation is critical to human functioning. Indeed, observational learning has particular significance in medical education in that it provides the context for which the importance and meaning of role models can be understood. In addition, as theoretical constructs such as self-efficacy and outcome expectancies allow us to establish an effective learning environment, exploring the concepts of the theory could be beneficial to medical education practice. In this context, the present review article aims to provide a glimpse of the fundamental assumptions and theoretical concepts of social cognitive theory and discusses the implications the theory has on teaching and learning. Further, a review of previous studies could help explain how the theory has informed medical education practice. Finally, the author will conclude with the implications and limitations of applying social cognitive theory in medical education.